Increase in Electrical Parameters Using Sucrose in Tomato Waste - Flores Segundo , Rojas (2022)
The use of organic waste as fuel for energy generation will reduce the great environmental problems currently caused by the consumption of fossil sources, giving agribusiness companies a profitable way to use their waste. In this research, tomato waste with different percentages of sucrose (0-target, 5, 10, and 20%) was used in microbial fuel cells manufactured on a laboratory scale with zinc and copper electrodes, managing to generate maximum peaks of voltage and a current of 1.08 V and 6.67 mA in the cell with 20% sucrose, in which it was observed that the optimum operating pH was 5.29, while the MFC with 0% (target) sucrose generated 0.91 V and 3.12 A on day 13 with a similar pH, even though all the cells worked in an acidic pH. Likewise, the cell with 20% sucrose had the lowest internal resistance (0.148541 ± 0.012361 KΩ) and the highest power density (224.77 mW/cm2) at a current density of 4.43 mA/cm2, while the MFC with 0% sucrose generated 160.52 mW/cm2 and 4.38 mA/cm2 of power density and current density, respectively, with an internal resistance of 0.34116 ± 0.2914 KΩ. In this sense, the FTIR (Fourier-transform infrared spectroscopy) of all the substrates used showed a high content of phenolic compounds and carboxylate acids. Finally, the MFCs were connected in a series and managed to generate a voltage of 3.43 V, enough to light an LED (green). These results give great hope to companies and society that, in the near future, this technology can be taken to a larger scale. View Full-Text